Novel phytochemical antibiotic conjugates as multitarget inhibitors of pseudomononas aeruginosa GyrB/ParE and DHFR - Jayaraman, Premkumar (2014)
Background: There is a dearth of treatment options for community-acquired and nosocomial Pseudomonas infections due to several rapidly emerging multidrug resistant phenotypes, which show resistance even to combination therapy. As an alternative, developing selective promiscuous hybrid compounds for simultaneous modulation of multiple targets is highly appreciated because it is difficult for the pathogen to develop resistance when an inhibitor has activity against multiple targets. Methods: In line with our previous work on phytochemical–antibiotic combination assays and knowledge-based methods, using a fragment combination approach we here report a novel drug design strategy of conjugating synergistic phytochemical–antibiotic combinations into a single hybrid entity for multi-inhibition of P. aeruginosa DNA gyrase subunit B (GyrB)/topoisomerase IV subunit B (ParE) and dihydrofolate reductase (DHFR) enzymes. The designed conjugates were evaluated for their multitarget specificity using various computational methods including docking and dynamic simulations, drug-likeness using molecular properties calculations, and pharmacophoric features by stereoelectronic property predictions. Results: Evaluation of the designed hybrid compounds based on their physicochemical properties has indicated that they are promising drug candidates with drug-like pharmacotherapeutic profiles. In addition, the stereoelectronic properties such as HOMO (highest occupied molecular orbital), LUMO (lowest unoccupied molecular orbital), and MEP (molecular electrostatic potential) maps calculated by quantum chemical methods gave a good correlation with the common pharmacophoric features required for multitarget inhibition. Furthermore, docking and dynamics simulations revealed that the designed compounds have favorable binding affinity and stability in both the ATP-binding sites of GyrB/ParE and the folate-binding site of DHFR, by forming strong hydrogen bonds and hydrophobic interactions with key active site residues. Conclusion: This new design concept of hybrid “phyto-drug” scaffolds, and their simultaneous perturbation of well-established antibacterial targets from two unrelated pathways, appears to be very promising and could serve as a prospective lead in multitarget drug discovery.